2009
DOI: 10.1108/18363261080001595
|View full text |Cite
|
Sign up to set email alerts
|

Do learner’s gender and ethnicity really matter for academic performance evaluation

Abstract: This study aims to determine whether different perceptions based on a learner’s characteristics of age, gender, ethnicity, and duration of stay in Australia provide an explanation of teaching performance evaluations. Perceptions determine interpersonal behaviour (including communication and motivation)and the way a learner believes that they are going to be assessed by the teacher. Thereby, this will impact on a student’s formal evaluation of teaching performance through a student survey of teaching (SST). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Therefore, an instructor's perceptions are essentially based on assumptions that are viewed as being true and thereby lead to stereotyping (2009). Other studies (Alexander-Snow, 2004;Prato & Espinoza, 2001) have illustrated that cultural stereotypes do in fact have an influence on perceptions in the classroom by both the student and instructor (as cited in Shauki, et al, 2009). …”
Section: Implicit Bias In the Classroommentioning
confidence: 97%
“…Therefore, an instructor's perceptions are essentially based on assumptions that are viewed as being true and thereby lead to stereotyping (2009). Other studies (Alexander-Snow, 2004;Prato & Espinoza, 2001) have illustrated that cultural stereotypes do in fact have an influence on perceptions in the classroom by both the student and instructor (as cited in Shauki, et al, 2009). …”
Section: Implicit Bias In the Classroommentioning
confidence: 97%
“…They found that female students tended to give higher SET scores than male students (Ali & Ajmi, 2013;Al-Issa & Sulieman, 2007;Batten et al, 2013;Beuth et al, 2015;Driscoll & Cadden, 2010;Narayanan et al, 2014;Kozub, 2010;Shauki et al, 2009;Whitworth et al, 2002;Worthington, 2002).…”
Section: Gendermentioning
confidence: 99%
“…Different studies indicate that SET scores are affected by some of the characteristics of the course and/or student (Al-Issa &Sulieman, 2007;Ali & Ajmi, 2013;Batten, Birch, Wright, Manley, & Smith, 2013;Beuth et al, 2015;Galbraith, Merrill, & Kline, 2012;Narayanan et al, 2014;Kozub, 2010;Pounder, 2007;Shauki, Ratnam, Fiedler, & Sawon, 2009;Whitworth et al, 2002;Worthington, 2002). These characteristics were: gender, student status, course type, course level, and academic school.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations